(untitled) (The Review of Diabetic Studies, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by persistent hyperglycemia and systemic inflammation, which significantly increases susceptibility to periodontal disease. Periodontitis, a chronic inflammatory condition of the supporting tissues of the teeth, is now recognized as both a complication and a modifier of diabetes, contributing to poor glycemic control and increased risk of systemic complications. Despite this bidirectional relationship, periodontal disease often remains undiagnosed in individuals with T2DM, particularly in non-dental healthcare settings. Nurses, as frontline providers in diabetes management, are uniquely positioned to contribute to early identification of periodontal disease risk. Objective: This narrative literature review aims to explore the role of point-of-care (POC) inflammatory biomarkers in supporting nursing-led screening for periodontal disease risk among patients with T2DM, emphasizing interprofessional integration between nursing, laboratory diagnostics, and periodontal care. Methods: A narrative synthesis of the literature was conducted using major biomedical and nursing databases, focusing on studies addressing inflammatory biomarkers, point-of-care testing, periodontal disease, and diabetes care. Emphasis was placed on biomarkers measurable through rapid or near-patient testing methods and their feasibility within nursing-led clinical settings. Results: Emerging evidence suggests that inflammatory biomarkers such as C-reactive protein (CRP), matrix metalloproteinase-8 (MMP-8), interleukins, and calprotectin reflect periodontal inflammatory burden and may be detected using point-of-care assays. These biomarkers demonstrate potential utility in identifying individuals at increased periodontal disease risk, particularly among patients with T2DM who exhibit heightened inflammatory responses. Nursing-led implementation of POC testing offers a practical approach to bridging gaps between medical and dental care, promoting early referral and integrated management. Conclusion: Point-of-care inflammatory biomarker testing represents a promising adjunct to nursing-led screening strategies for periodontal disease risk in patients with T2DM. Integrating such approaches into diabetes care pathways may enhance early detection, interdisciplinary collaboration, and overall patient outcomes. Further research is needed to standardize biomarker thresholds, validate nursing workflows, and assess long-term clinical impact.